Pemikiran Andreas Harsono Dalam Buku Agama Saya Adalah Jurnalisme: Penguatan Jurnalisme Profesional Di Era Transformasi Digital - Eva Andini; Nurseri Hasnah Nasution; Muslimin . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the thoughts of Andreas Harsono in the book My Religion is Journalism and their relevance to strengthening professional journalism in the era of digital transformation. The background of this research is based on the dynamics of digital media development, which has brought significant changes to journalistic practices, such as the rapid flow of information, the increasing spread of hoaxes, and challenges to the integrity and professionalism of journalists. This research employs a qualitative approach using a library research method. The primary data source is the book My Religion is Journalism, while secondary data are obtained from relevant literature such as academic journals, books, and other credible sources. The data analysis technique used is content analysis, which examines the main ideas proposed by Andreas Harsono regarding the fundamental values of journalism, including commitment to truth, independence, verification, and responsibility to the public. The results show that Andreas Harsono emphasizes the importance of integrity as the main foundation in professional journalism practices. In the era of digital transformation, these values have become increasingly crucial in maintaining media credibility amid the overwhelming flow of information. Strengthening professional journalism can be achieved through improving the quality of information verification, mastering digital technology, and consistently upholding the journalistic code of ethics. Therefore, Andreas Harsono’s thoughts in the book My Religion is Journalism remain highly relevant in building and strengthening professional journalism in the face of digital-era challenges.